Case Report: Successful multimodal management of FIRES in a pediatric patient using anakinra, ketogenic diet, and induced hypothermia - Caporale, Mariagiovanna; Lais, Giulia; Gulli’, Antonio; Caporale, Carla; Piastra, Marco; Conti, Giorgio (Frontiers in Pediatrics, 2025)
Febrile infection–related epilepsy syndrome is a devastating, refractory epileptic encephalopathy that typically occurs in school-aged, otherwise healthy, children after a brief, non-specific, febrile illness. In this study, we discuss a case of a previously healthy 10-year-old girl with FIRES in whom high dosages of conventional and non-conventional antiepileptic drugs were ineffective in treating refractory status epilepticus, after which a treatment involving intravenous corticosteroids, immunoglobulins, a ketogenic diet, and induced hypothermia was adopted. We conducted a diagnostic workup that included lumbar puncture, blood tests, continuous electroencephalogram monitoring, brain MRI, and autoimmunity and infectious disease panels to shed light on the etiology of the condition. Our patient responded to immunosuppressive therapy and the ketogenic diet, and her condition gradually improved to full recovery with only mild neurocognitive sequelae. Although patients with FIRES have been described in the literature, optimal management has not yet seen the light of day, and therefore, prospective cohort studies are needed. This case highlights the potential benefit of a timely, multimodal therapeutic approach combining immunomodulation, metabolic support, and neuroprotection. Early administration of anakinra and initiation of a ketogenic diet may help control seizures and reduce the duration of ICU stay. Prompt diagnosis and interdisciplinary care are essential to improve outcomes in patients with this life-threatening pediatric condition.